Faktor-Faktor yang Mempengaruhi Work Life Balance Perawat: A Rapid Narrative Review - Widayana, I Gede Angga Ariesta; Agustina, Hana Rizmadewi; Mediawati, Ati Surya (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT The nursing profession demands high physical and emotional endurance, with long working hours, unpredictable schedules, and pressure that can disrupt work-life balance. This imbalance poses risks to well-being, job satisfaction, and the quality of healthcare services. This narrative review aims to identify the factors influencing the work-life balance among nurses in hospital. A rapid narrative review was conducted following the PRISMA 2020 guidelines, analyzing nine articles from the PubMed, EBSCO, and Scopus databases. The review findings indicate that work schedules, social support, organizational policies, and psychological factors such as burnout and emotional resilience affect nurses’ work-life balance. Flexible policies and adequate support have been proven to enhance their well-being and job satisfaction. Flexible policies and adequate support can improve nurses’ well-being and service quality. Healthcare institutions need effective strategies to address work-life imbalance. Keywords: Hospital, Nurses, Work-Life Balance. ABSTRAK Profesi keperawatan menuntut fisik dan emosional yang tinggi, dengan jam kerja panjang, jadwal tidak menentu, dan tekanan yang dapat mengganggu keseimbangan kehidupan kerja dan pribadi. Ketidakseimbangan ini berisiko menurunkan kesejahteraan, kepuasan kerja, serta kualitas layanan kesehatan. Tinjauan naratif ini bertujuan mengidentifikasi faktor-faktor yang mempengaruhi work life balance perawat di rumah sakit. Metode yang digunakan adalah tinjauan naratif cepat berdasarkan pedoman PRISMA 2020, dengan analisis 9 artikel dari basis data PubMed, EBSCO, dan Scopus. Hasil kajian menunjukkan bahwa jadwal kerja, dukungan sosial, kebijakan organisasi, serta faktor psikologis seperti burnout dan ketahanan emosional memengaruhi keseimbangan kehidupan kerja perawat. Kebijakan fleksibel dan dukungan yang memadai terbukti meningkatkan kesejahteraan dan kepuasan kerja mereka. Kebijakan fleksibel dan dukungan yang dapat meningkatkan kesejahteraan perawat serta kualitas layanan. Institusi kesehatan membutuhkan strategi efektif untuk mengatasi ketidakseimbangan antara pekerjaan-kehidupa pribadi Kata Kunci: Keseimbangan Kehidupan Kerja dan Pribadi, Perawat, Rumah Sakit.